Electron transport in double bridges system - Abdul-Hussein, W. A.; Abd, J S (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper we investigate theoretically the effect of introducing wide band, and Narrow band approximations for the bridge energy band on the electron transport process (ET) through the donor-bridges-acceptor (DBA) system. We using one electron model, for which the Hamiltonian of the system consists of a single-level for both Donor and Accepter (i.e. QD) both coupled to a band bridge as a tight binding interaction. The time dependent Schrödinger equation give us a formula for the occupation probabilities for donor and acceptor levels. The probability of (ET) to the donor and accepter is small because the electron accumulated on the bridge units. Also, the current of acceptor and the effect of different system parameters are studied.